2021
DOI: 10.2144/fsoa-2020-0197
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase-type Plasminogen Activator Receptor Strongly Predicts Global Mortality in Acute Heart Failure Patients: Insight From the STADE-HF Registry

Abstract: Background: Whether soluble urokinase-type plasminogen activator receptor (suPAR) could be a valuable prognostic indicator remains uncertain. Materials & methods: Patients from STADE-HF (Soluble Suppression of Tumorigenesis-2 as a Help for Management of Diagnosis, Evaluation and Management of Heart Failure) were included for analysis. Results: 95 patients were included. The suPAR level of expression was significantly higher in the group of patients who died at one month (7.90 ± 4.35 ng/ml vs 11.94 ± 6.86 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Here, we extended these observations using mass spectrometry analysis to demonstrate that serum EVs after TBI contain myriad inflammasome-, complement-and cardiovascular-related signaling proteins. Some of the proteins found in EVs have been implicated in inflammasome signaling such as the complement C3 [48] and C5 proteins [34], while others are also involved in cardiovascularrelated events like ceruloplasmin [37], clusterin [33], plasminogen [35], kininogen [38] or haptoglobin [36]. In particular, the complement component C3 was abundantly present in serum-derived EVs after TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we extended these observations using mass spectrometry analysis to demonstrate that serum EVs after TBI contain myriad inflammasome-, complement-and cardiovascular-related signaling proteins. Some of the proteins found in EVs have been implicated in inflammasome signaling such as the complement C3 [48] and C5 proteins [34], while others are also involved in cardiovascularrelated events like ceruloplasmin [37], clusterin [33], plasminogen [35], kininogen [38] or haptoglobin [36]. In particular, the complement component C3 was abundantly present in serum-derived EVs after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected a variety of proteins that have been described to be involved in inflammasome signaling, such as complement C5, serotransferrin, complement factor H, complement C4-B and complement factor B, which were elevated in the TBI group when compared to sham mice (Figure S3C). Finally, we also identified the following signaling proteins that have been shown to be involved in cardiac-related signaling events, such as ceruloplasmin, clusterin, plasminogen, kininogen-1, haptoglobin and inter alpha-trypsin inhibitor heavy chain H2, which were elevated in the TBI group when compared to the sham group (Figure S3D) [33][34][35][36][37][38].…”
Section: Serum-derived Ev Characterization After Tbimentioning
confidence: 99%
“…Soluble urokinase plasminogen activator (suPAR) is an inflammatory biomarker that robustly predicts adverse cardiovascular events and mortality in patients with cardiovascular disease [ 18 20 ]. Furthermore, suPAR is shown to have prognostic utility among cancer patients, particularly breast cancer [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…They proved that suPAR levels were independently associated with mortality at 1 month and 1 year for patients with acute HF, but without significant prediction of the hospitalization risk and it was a stronger predictor for mortality than other biomarkers (sST2, NT-proBNP or CRP). 34 Bengaard et al described an overall risk of readmission and mortality significantly increased for patients with higher suPAR, 55 while Al-Badri et al showed that high suPAR and hsTnI levels were independently associated with a higher risk of all cause death and MACE. 56 Moreover, hs-CRP, NT-proBNP, and suPAR showed different associations with cardiovascular death among apparently healthy younger and older men and women.…”
Section: Suparmentioning
confidence: 99%
“…33 Furthermore, in the STADE-HF study, an ancillary study of a randomized trial: NCT02963272, sST2 showed to be better associated with the risk of hospitalization when compared to suPAR, which, in contrast, resulted associated with long term mortality. 34 It was also revealed that sST2-guided therapy does not decrease readmissions. This study was aimed to evaluate a sST2-guided treatment in patients hospitalized for acute HF.…”
Section: Introductionmentioning
confidence: 99%